A functional start to computing with Python - Herman, Ted, 1952- (Chapman & Hall/CRC, 2013)
Annotation Open source and easy to use, Python offers the availability of exciting libraries of software, application programming interfaces, and even connections to web services. This textbook uses Python as a working environment to teach the basics of computing for students with no prior programming experience.
Keywords: Python (Computer program language); elektronické knihy; electronic books